THE PRINCIPLE OF THE PRESUMPTION OF INNOCENCE IN LIGHT OF THE (IN)CONSTITUTIONALITY OF ART. 492, ITEM I, LINE “e” OF THE CRIMINAL PROCEDURE CODE. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article aims to analyze the constitutionality of the immediate execution of the sentence in the jury trial, as worded in art. 492, and the Code of Criminal Procedure, incorporated by law 13964/19. On the one hand, there is the slowness of the judiciary, linked to the management of resources in a protracted manner and the social outcry for an effective judicial response, especially linked to intentional crimes against life, on the other hand, there is the need to preserve the principle of the presumption of innocence, so as not to restrict the freedom of those who have not yet been duly convicted and found guilty under the terms of the law. Further, it is necessary to analyze the evident conflict of constitutional principles, on the one hand the presumption of innocence and the double degree of jurisdiction and on the other hand the Sovereignty of Verdicts. That said, analyzes will be made regarding the numerous changes in jurisprudence of the Federal Supreme Court regarding the ideal moment for executing the sentence, noting that, in no way can the damage caused to someone who wrongly had their freedom curtailed be reversed. This work is based on bibliographical research through monographs, master's theses, doctoral theses, scientific articles, legislation and court decisions.